The Transfer of China’s Energy-Intensive Industries Under Environmental Regulation: An Evolutionary Game Theory Approach Based on Sustainable Development - Liming Hu; Huilin Wang; Xinyi Cai (SAGE Open)
As energy-intensive industries significantly impact the ecological environment, they serve as both foundational sectors for national economic development and cornerstones for ensuring the security and stability of industrial and supply chains. These industries are critical for promoting regional sustainable development. Considering the multiple challenges posed by the development of energy-intensive industries in China, such as environmental governance and energy supply issues, this study aims to explore how local governments can use environmental regulation to address these challenges. Using evolutionary game theory, this paper constructs an evolutionary game model between local governments and energy-intensive enterprises in China. The model examines the equilibrium points and their stability in their strategic interactions. MATLAB simulations are employed to illustrate how non-ideal equilibrium states can evolve into ideal equilibrium states. The findings reveal four equilibrium states in the game between local governments and energy-intensive enterprises: undesirable, worst, suboptimal, and ideal. The initial intentions of participants do not affect the equilibrium state of the system. However, selectively adjusting other cost-benefit variables in the model can guide the system from undesirable, worst, or suboptimal equilibrium states toward the ideal equilibrium state. This study not only deepens the understanding of industrial transfer research but also provides novel insights for local governments to leverage environmental regulation in designing policies that promote regional sustainable development.